A Review of Rituals and Local Wisdom of Indigenous Peoples in Indonesia - Sulkhan Chakim (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
This study aims to map publication trends about the rituals, and local wisdom of indigenous peoples in Indonesia published at the international level, can provide benefits for researchers about traditions and local wisdom, is 1) mapping specifications of research developments, 2) revealing research collaborations and publications at the global level. The method used in this study is a bibliometric method that can provide guidelines for citation analysis, co-citation, coupling bibliometric, and shared word analysis. This bibliometric method has completed the meta-analysis and review of the constructed literature to explore and evaluate the scientific publications that researchers have carried out. The results showed that investigations related to indigenous peoples' rituals and local wisdom were demonstrated by 48 events, six items and 12 links, 3 clusters, including cluster 1 consisting of human, Indonesian and local wisdom. Cluster 2 consists of ecotourism and sustainability. Cluster 3 includes a questionnaire survey, widely published by the database scopus.com from 2012 to 2022. Mapping done through bibliometrics shows that research trends related to human keyword terms have been widely developed and published over the past ten years.